Mastering Apache Sqoop : a hands-on guide to transferring data between Hadoop and relational databases - Yahalom, David (O'Reilly, 2016)
"In this Mastering Apache Sqoop training course, expert author David Yahalom teaches you everything you need to know about Apache Sqoop. This course is designed for the absolute beginner, meaning no previous experience with Sqoop is required. You will start by learning what Sqoop is used for, including data analysis, data archival, and data consolidation. From there, David will teach you how to import data to Hadoop from a relational database. This video tutorial also covers how to export data from Hadoop to a relational database. Finally, you will cover advanced Sqoop topics. Once you have completed this computer based training course, you will have learned everything you need to know about Apache Sqoop."--Resource description page.